Retropubic Cartilaginous Cyst: A Rare Entity - Matos, Inês (2023)
A pubic cartilaginous cyst is a rare, benign, slow-growing degenerative lesion arising from the fibrocartilaginous part of the pubic symphysis joint usually occurring in post-menopausal women. It should be considered in the differential diagnosis of pubic and vulvar cystic masses. Since it is an uncommon lesion, especially in men, it can be easily misdiagnosed. Magnetic Resonance imaging is the investigation of choice for this condition. We report a case of a retropubic cyst incidentally detected in a 57-year-old male patient who performed a left hip Magnetic Resonance imaging.